The World Distribution of Income and Income Inequality - Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
This review covers a range of measures and methods frequently employed in empirical analysis of global income inequality and global income distribution. Different determinant factors along with quantification of their impacts and empirical results from different case studies are presented. These results are further contrasted to those obtained based on the World Income Inequality Database. A number of issues crucial to the studies of global income inequality are addressed. These are the concepts, measurement and decomposition of inequality, the world distribution of income and inequality measured at different levels of aggregation: global, international and intra-national. We analyse income at each of the three levels, discuss the benefit and limitations of each approach and present empirical results found in the literature and compare it with those based on the World Income Inequality Database. Research on the world income inequality supports increased awareness of the problem, its measurement and quantification, identification of causal factors and of policy measures to affect global income inequality.
Keywords: N30; I30; D63; D31; C10; 330; global income inequality; income distribution; inequality indices; Einkommensverteilung; Disparitätsmass; Welt